Infected cephalhaematoma causing osteomyelitis: case report and literature review. Issue 5 (27th May 2022) - Baig Mirza, Asfand; Boardman, Timothy; Ashworth, Samantha; Al-Faiadh, Wisam; Ahmed, Razna; Lavrador, José Pedro; Maratos, Eleni; Chandler, Chris; Bleil, Cristina; Zebian, Bassel
Abstract: Infected cephalhaematomas are rare and can lead to complications such as sepsis, meningitis and osteomyelitis. We present an infected cephalhaematoma in a neonate with resultant underlying osteomyelitis and a review of the literature. Our patient presented 6 days following birth with a fever and a swelling consistent with cephalhaematoma. He was managed with intravenous antibiotics and early surgical intervention. Imaging demonstrated underlying osteomyelitis. The patient made a full recovery and was discharged home on completing his antibiotic course. On reviewing the literature, it is clear that early diagnosis and treatment with surgical intervention and antibiotic therapy are associated with improved outcome and can reduce the possibility of osteomyelitis developing.